Evidence for the effectiveness of pomegranate supplementation for blood pressure management is weak: A systematic review of randomized clinical trials - Gbinigie, O; Onakpoya, I; Spencer, E (Elsevier, 2017)
Hypertension is one of the most important preventable causes of premature death. Studies have been conducted assessing the impact of pomegranate on blood pressure, with varying results. The aim of this review was to critically appraise and evaluate the effect of pomegranate on blood pressure in adults, using evidence from randomized clinical trials (RCTs). We conducted electronic searches in Medline, Embase, Amed, and The Cochrane Library, and included RCTs assessing the effectiveness of pomegranate on blood pressure. We assessed the reporting quality using the Cochrane criteria. We included 8 RCTs comprising 619 participants. The studies varied in their reporting quality, and compared pomegranate juice or capsules with a control. Two studies reported significant reductions in systolic blood pressure favoring pomegranate: p = .002 and p < .001 respectively; 3 studies reported no significant differences between groups; and 3 studies failed to report between-group differences. Two studies reported significant reductions in diastolic blood pressure favoring pomegranate: p = .038, p < .001, respectively; 4 studies reported no significant between-group differences; and 2 studies did not report between group differences. No adverse events were observed. The limited evidence from clinical trials to date fails to convincingly show a beneficial effect of pomegranate on blood pressure. We have identified evidence gaps and highlight areas for future research to be conducted, including performing studies of high quality and longer duration.